Trends in Peripheral Nerve Epidemiology and Reconstruction: A State Database Study of Direct Repairs, Grafts, and Conduits. Issue 2 (August 2021) - Bellaire, Christopher P.; Inglesby, Dani C.; Marayati, Naoum Fares; Warburton, Andrew J.; Melamed, Eitan
Abstract : Background: Peripheral nerve injuries (PNIs) are most commonly treated with direct nerve repair procedures or nerve autografts. However, recent advancements in synthetic and vein conduits have led to their increased utilization. The present study quantifies the incidence of these procedures over time and geography and identifies differences in complication rates, illustrating the current epidemiologic climate regarding conduit use for PNI repair. Methods: A query was conducted using the State Ambulatory Surgery and Services Databases data from 2006 to 2011 in both Florida and California for patients undergoing nerve repair, nerve grafting, synthetic conduits, and vein conduits. Patient zip code data were analyzed to determine the geographic distribution of various types of repair. In addition, text-mining algorithms were used to identify trends in PNI-related publications. Results: In the 6-year period investigated, direct nerve repair was the most frequently used procedure for PNIs. However, the utilization of direct repairs declined significantly from 2006 to 2011. Synthetic and vein conduits demonstrated a significant increase over the same period. There were significantly higher rates of complications for autologous grafts (3.3%), vein conduits (3.5%), and synthetic conduits (2.4%), as compared with direct nerve repairs (1.4%). There was a nonsignificant difference in infection rates between these types of nerve repair. Conclusions: From an epidemiologic perspective, both graft and synthetic conduit-based PNI repairs are increasing in prevalence both in clinical practice and in the academic literature. This will likely continue in the future with the development of advancements in biologic and synthetic nerve conduit PNI repair options.